Treatment of osteoporosis with recombinant parathyroid hormone, its effects on bone, total body muscle and fat composition and factors determining response to this therapy - Siddique, Najia (Trinity College (Dublin, Ireland). School of Medicine. Discipline of Medical Gerontology, 2015)
Total body bone mineral density (BMD) is relatively underutilised as an assessment tool for osteoporosis. Studies to date on Body composition have not clearly identified key factors which contribute to total body BMD, muscle mass and fat mass in osteoporotic patients. In addition, the effect of certain treatments for osteoporosis i.e., recombinant Parathyroid hormone (PTH) on these total body parameters remains under investigated. Furthermore clinical factors and assessment tools that determine optimal response to PTH have to be clarified. Lastly role of Quantitative heel ultrasound (QUS) in severely osteoporotic patients attending bone health clinic (BHC) remains to be evaluated.
Keywords: Gerontology, M.D.; M.D. Trinity College Dublin